BREAKING FREE: EDNA PONTELLIER AND ETHAN FROME - Melani Hadžić; Anđelka Raguž (Hum, 2015)
Social norms and conventions are often presented in literature as limitations which curb the protagonists’ personal development. When personal desires clash with societal expectations, the struggle to forge an identity for themselves constitutes the conflict in these literary works. Two such works are Kate Chopin’s The Awakening and Edith Wharton’s Ethan Frome. Both Edna Pontellier and Ethan Frome feel oppressed by social conventions and try to break free from the chains society has placed on them. This paper will examine and analyse Edna Pontellier’s and Ethan Frome’s relationship to their respective societies, their attempts to rebel and the success of their endeavours to break free. It will consequently show that irrespective of the society in question and the gender of the protagonist, social conventions are iron-forged manacles that cannot be easily broken, leaving the protagonists of these works with one option: early death.